Updating Chinese SO2 emissions with surface observations for regional air-quality modeling over East Asia - Bae, Changhan; Kim, Hyun Cheol; Kim, Byeong Uk; Kim, Younha; Woo, Jung Hun; Kim, Soontae (Atmospheric Environment, 2020)
Anthropogenic emissions in East Asia have changed dramatically in recent years. To measure these changing emissions in support of air-quality modeling, we developed a top-down emission update system using surface observations and a geographical information system spatial-allocation technique. We deploy a data-processing system to construct adjustment factors to prefecture-level SO2 emissions by comparing surface and modeled observations. A case study is conducted over East Asia for 2016 in which we update Chinese SO2 emissions using measurements from around 1500 surface monitoring sites. Model simulations using updated SO2 emissions are improved relative to the existing simulation system (e.g., R = 0.23 to R = 0.8), suggesting that the newly designed system provides an efficient, practical forecast solution. Finally, estimated SO2 emissions are compared with existing emission inventories, agreeing well with recent reports of reduced SO2 emissions from Chinese anthropogenic sources.
Keywords: Air quality modeling; Anthropogenic emissions; Anthropogenic sources; Data processing systems; Emission inventories; Regional air quality modeling; Surface monitoring; Surface observation; East Asia air quality; SO2 emissions inventory; Top-down emission adjustment